2009
DOI: 10.1099/vir.0.009647-0
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of Prunus necrotic ringspot virus: hitch-hiking from gametes to seedling

Abstract: The aim of this work was to follow Prunus necrotic ringspot virus (PNRSV) infection in apricot reproductive tissues and transmission of the virus to the next generation. For this, an analysis of viral distribution in apricot reproductive organs was carried out at different developmental stages. PNRSV was detected in reproductive tissues during gametogenesis. The virus was always present in the nucellus and, in some cases, in the embryo sac. Studies within infected seeds at the embryo globular stage revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 44 publications
(47 reference statements)
1
22
0
1
Order By: Relevance
“…ALSV in pollen and embryo sacs might therefore be inactivated during fertilization and/or seed maturation. In apricot infected with PNRSV, not all pollen grains were infected, but the virus was always present in the nucellus and sometimes present in the embryo sac of female reproductive organs (Amari et al 2007(Amari et al , 2009). In contrast, in apple, ALSV was detected in most pollen grains and in all embryo sacs, but barely detectable in the nucellus of infected apple flower buds.…”
Section: Discussionmentioning
confidence: 99%
“…ALSV in pollen and embryo sacs might therefore be inactivated during fertilization and/or seed maturation. In apricot infected with PNRSV, not all pollen grains were infected, but the virus was always present in the nucellus and sometimes present in the embryo sac of female reproductive organs (Amari et al 2007(Amari et al , 2009). In contrast, in apple, ALSV was detected in most pollen grains and in all embryo sacs, but barely detectable in the nucellus of infected apple flower buds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated also that seed transmission is related to the ability of the virus to infect flower organs, especially the meristematic reproductive tissue, during early developmental stages [34]. Similarly, Amari et al [35] have demonstrated that Prunus necrotic ringspot virus (PNRSV) invades apricot reproductive organs, including the pollen mother cell stage, early in development, and after that PNRSV infects all parts of the seed, including embryo, endosperm and testa, shedding light on the vertical transmission of PNRSV from gametes to seedlings [1]. Also the wide natural incidence of the nepovirus Cherry leaf roll virus (CLRV) is believed to have occurred mainly by seed transmission, in fact vertical transmission of CLRV by seed and pollen has been reported to occur naturally by embryo invasion in different works [36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, much research has focused on the routes by which the seeds become infected and on the progress of viral infection in reproductive organs during their development up until the seedling stage [1,7,24]. Few researchers have addressed the problem of the correlation between breeding techniques and seed transmission of viruses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations